Flexible chiral pyrazolate-based metal–organic framework containing saddle-type CuI4(pyrazolate)4 units. Issue 40 (3rd October 2016) - Grzywa, Maciej; Denysenko, Dmytro; Schaller, Andreas; Kalytta-Mewes, Andreas; Volkmer, Dirk
Abstract : CFA-9, a chiral MOF containing saddle-type Cu I 4 (pyrazolate)4 units, shows reversible breathing behavior and exhibits binding of CO. Abstract : The syntheses and crystal structures of [Cu I 2 (phbpz)]·MeOH (lp-CFA-9, lp = large-pore) and [Cu I 2 (phbpz)] (np-CFA-9, np = narrow-pore; H2 -phbpz = 3, 3′, 5, 5′-tetraphenyl-1 H, 1′ H -4, 4′-bipyrazole) are described. The copper(i )-containing metal–organic framework (termed C̲oordination F̲ramework A̲ugsburg University-9, lp-CFA-9 ) crystallizes in the trigonal crystal system, within the chiral space group P 32 21 (no. 154) and with the following unit cell parameters: a =18.2348(6), c = 16.3950(4) Å, and V = 4721.1(2) Å 3 .Lp-CFA-9 features a 3-D microporous framework structure of Cu4 pz4 (pz = pyrazolate) SBUs with the D 2d (= 4̄2 m ) symmetry connected by single bonds creating one-dimensional channels expanding in the c -direction of the crystal lattice. The framework flexibility ofCFA-9 has been demonstrated by single-crystal and powder X-ray analyses as well as by sorption measurements.CFA-9 exhibits weak binding of carbon monoxide on Cu(i ) centers. The reactivity ofCFA-9 towards oxidizing agents, such as H2 O2, t -BuOOH and Br2 was also investigated. Additionally, CFA-9 shows luminescence upon exposure to UV radiation.